Microfinance Management System Human Resource: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Microfinance Human Resource I project is a web-based system that offers several HRservices, including competency management, recruitment and applicant management,learning and training management, newly hired onboarding, employee self-service,performance management, social recognition, and succession planning. Some organizationsutilize human resources for effective decision-making processes. However, they struggle withproductivity due to various issues, including manual data collection, lack of email verification,and improper storage of confidential information. To resolve the problem, the project teamdeveloped a web-based system to support and manage the organization by reducing time-fillproductivity, securing data, and boosting workforce engagement to improve productivity andmake a significant employee commitment.The project team employed agile methodologies to ensure the prompt completion of HRmanagement tasks and prioritized the production of high-quality deliverables. Consequently,The Project team created a web-based system that efficiently streamlines and managesvarious HR operations, such as email communication, secure data management, and amanageable shortlisting process. These accomplishments have led to notable improvementswithin the organization.The web-based platform Microfinance Management System Human Resource 1 focuses onimproving various processes to create better transactions, enhance data security, and fill thegap so that each process inside the organization is more convenient and organized.
Keywords: IT & Management